Appraising Efficacy of Cognitive Pain Management Strategies for the Rehabilitation of Non-Chronic Sciatica: A Randomized Control Trial - Pratik A Gohil; Anjali Gohil (RGUHS Journal of Physiotherapy)
Background Low back ache receives considerable attention in the medical field due to its high occurrence in civil society. Despite its high occurance rate there is no clear conservative treatment approach available. This has motivated many researchers to delve further into the study of lower back ache. Thus after an extensive review of literature this study has chosen non-chronic sciatica from the vast domain of low back ache to establish possible treatments so as to address the problem before it becomes chronic.Objectives To determine the effectiveness of cognitive pain management strategies in improving pain as determined by McGill pain questionnaire SF-MPQ-2 scores among non-chronic cases of sciatica.Methodology Thirty patients in the age group of 40 to 60 years who were clinically diagnosed with non-chronic sciatica and fulfilled inclusion and exclusion criteria were divided randomly into two equal groups. One group received a conventional physical therapy approach while the other group received cognitive pain management strategies along with conventional management for a two-week period and the outcome on pain was assessed.Results A paired t-test was used to find the difference between pre and post-treatment. It showed statistically relevant changes in the SF-MPQ-2 scores in the experimental group which used cognitive pain management strategies. T-value was 3.70557 and the P-value was 0.00092. The result was significant at P lt0.05.Conclusion This study concludes that adding cognitive pain management strategies into existing physical therapy practice provides better outcomes compared to the use of conventional physical therapy alone.